Raman spectra of InᵪTl₁₋ᵪI substitutional solid solutions - Dovhyi, Ya.O.; Ternavska, S.V.; Franiv, A.V.; Bovgyra, O.V.; Savchyn, O.V. (Functional Materials, 2005)
The structure of Raman spectra of InᵪTl₁₋ᵪI substitutional solid solutions (х = 0.2, 0.3, 0.4, 0.5, 0.7) oriented in the (а,с) plane has been studied. Basing on the group theory Analysis, the symmetry of phonon modes has been classified. The Fano anti-resonances have been revealed in the Raman spectra. The role of free carriers in the mechanism of essential changes in the phonon spectrum structure is discussed as depending on thallium content. Дослiджено структуру спектрiв комбiнацiйного розсiювання твердих розчинiв замiщення InᵪTl₁₋ᵪI (х = 0,2, 0,3, 0,4, 0,5, 0,7), орiєнтованих у площинi (а,с). На основi теоретико-групового аналiзу проведено класифiкацiю симетрii фононних мод. У спектрах виявлено антирезонанси Фано. Обговорюеться роль вiльних носiїв у механiзмi суттевих змiн структури фононних спектрiв у залежностi вiд вмiсту талiевоi компоненти. Исследована структура спектров комбинационных рассеяния твердых растворов замещения InᵪTl₁₋ᵪI (х = 0,2, 0,3, 0,4, 0,5, 0,7), ориентированных в плоскости (а,с). На основе теоретико-группового анализа проведена классификация симметрии фононных мод. Обнаружено антирезонансы Фано в спектрах. Обсуждается роль свободных носителей в механизме существенных изменений структуры фононных спектров в зависимости от содержания таллиевой компоненты.